Battery manufacturing method and battery
By using a clamp with multiple protruding fixtures to clamp the side members and forming holes in the resin layer in the thermal welding step, the poor bonding performance problem caused by poor ultrasonic vibration transmission in the prior art is solved, and efficient bonding between the current collector and the side members in the battery is achieved.
Patent Information
- Application Number
- JP2023005465
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-01-17
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-01-17
AI Technical Summary
In the prior art, when connecting the current collector to the side members, the transmission of ultrasonic vibrations is poor, resulting in poor bonding performance.
When manufacturing the battery, a plurality of protruding clamps are used to clamp the side members, so as to penetrate the resin layer and contact the side members surface, ensure that ultrasonic vibration energy is effectively transmitted to the contact surface, and holes of the resin layer are formed in the thermal welding step to enhance the anchoring effect.
Through improved fixture design and thermal welding steps, the bonding performance of the current collector to the side members in the battery is significantly improved, ensuring high-quality manufacturing of the battery.
Smart Images

Figure 0007661984000002 
Figure 0007661984000003 
Figure 0007661984000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for manufacturing a battery, and to a battery. [Background technology]
[0002] Conventionally, in a battery equipped with an electrode body having a current collector and a terminal, a method has been used in which the electrode body and the terminal are electrically connected by joining an end of the current collector to one surface of a side member. For example, Patent Document 1 discloses an ultrasonic bonding method for bonding multiple stacked current collecting foils and a current collecting terminal, in which the current collecting terminal has multiple protrusions formed on the surface facing the current collecting foil, and the multiple stacked current collecting foils and the current collecting terminal are welded and bonded by ultrasonic bonding. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2022-073690 Summary of the Invention [Problem to be solved by the invention]
[0004] Incidentally, when joining a current collector and a side member including a terminal, as shown in FIG. 6, for example, the current collector 6 is placed in contact with the side member 2, and a horn 12 is pressed against the current collector 6, and ultrasonic vibration is applied from the horn 12 to join them. At this time, a pair of clamps 24 are pressed against a pair of side surfaces 2B, 2C of the side member 2 from above the tab film 4 as a presser to hold and fix the side member 2. Here, conventionally, clamps 24 with a smooth surface pressed against the tab film 4 have been used. However, ultrasonic vibrations are not well transmitted to the interface between the joining surfaces of the current collector and the side member, which can result in poor joining performance.
[0005] The present disclosure has been made in consideration of the above-mentioned circumstances, and has an object to provide a manufacturing method for a battery and a battery that have excellent bonding performance between a current collector and a side member. [Means for solving the problem]
[0006] <1> An electrode assembly having a current collector; a side member including a terminal, the side member being disposed on a side surface of the electrode body, the side member having a joining surface to be ultrasonically joined to the current collector, and a pair of side surfaces adjacent to the joining surface; a resin layer disposed on a surface of the pair of side surfaces of the side surface member; A method for manufacturing a battery, comprising the steps of: a joining step of ultrasonically joining the current collector to the joining surface of the side member, the joining step is a step of ultrasonically joining the pair of side surfaces of the side surface member while holding the pair of side surfaces of the side surface member from above the resin layer with a pair of clamps having a plurality of protrusions, The method for manufacturing a battery, wherein the clamping is performed so that the protrusions of the clamp penetrate the resin layer and contact the pair of side surfaces. <2> the battery has a laminate sheet covering the electrode body and the side member, The joining step includes forming holes in the surfaces of the pair of side surfaces by the protrusions of the clamp during the holding step, A thermal welding step of thermally welding the laminate sheet and the side member is provided after the joining step, The resin of the resin layer has entered into the hole after the thermal welding process. <1> A method for manufacturing the battery according to claim 1. <3> An electrode assembly having a current collector; a side member including a terminal, the side member being disposed on a side surface of the electrode body, the side member having a joining surface that is ultrasonically joined to the current collector, and a pair of side surfaces adjacent to the joining surface; a resin layer disposed on a surface of the pair of side surfaces of the side surface member; a laminate sheet covering the electrode body and the side surface member and heat-welded to the side surface member; The side surface member has a plurality of holes on the pair of side surfaces, The resin of the resin layer penetrates into the holes. Effect of the Invention
[0007] According to the present disclosure, it is possible to provide a battery manufacturing method and a battery having excellent bonding performance between a current collector and a side member. [Brief description of the drawings]
[0008] [Figure 1] 3A to 3C are schematic cross-sectional views illustrating each step of a method for manufacturing a battery according to an embodiment of the present disclosure. [Diagram 2] 3A to 3C are schematic cross-sectional views illustrating each step of a method for manufacturing a battery according to an embodiment of the present disclosure. [Diagram 3] 3A to 3C are schematic cross-sectional views illustrating each step of a method for manufacturing a battery according to an embodiment of the present disclosure. [Figure 4] 3A to 3C are schematic cross-sectional views illustrating each step of a method for manufacturing a battery according to an embodiment of the present disclosure. [Diagram 5] 3A to 3C are schematic cross-sectional views illustrating each step of a method for manufacturing a battery according to an embodiment of the present disclosure. [Figure 6] FIG. 1 is a schematic cross-sectional view illustrating one step of a conventional battery manufacturing method. [Figure 7] FIG. 2 is a schematic perspective view showing only a side member of a battery according to an embodiment of the present disclosure. [Figure 8] FIG. 2 is a schematic plan view showing only a side member of a battery according to an embodiment of the present disclosure. [Figure 9] FIG. 2 is a schematic plan view showing only a side member of a battery according to an embodiment of the present disclosure. [Figure 10] FIG. 2 is a schematic plan view showing only a side member of a battery according to an embodiment of the present disclosure. [Figure 11] 3 is a schematic cross-sectional view showing an enlarged view of a hole formed in a side member of a battery according to an embodiment of the present disclosure. FIG. [Figure 12] FIG. 1 is a schematic cross-sectional view showing an example of a solid-state battery. [Figure 13] FIG. 2 is a schematic cross-sectional view for explaining a method for measuring a bonding strength in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The battery according to the present disclosure will be described in detail below with reference to the drawings. Each of the drawings shown below is a schematic illustration, and the size and shape of each part are appropriately exaggerated for ease of understanding.
[0010] <Battery manufacturing method> A method for manufacturing a battery according to an embodiment of the present disclosure will be described. In the battery manufacturing method, a battery is manufactured that has an electrode body having a current collector, a side member including a terminal, a bonding surface arranged on a side surface of the electrode body and ultrasonically bonded to the current collector, and a pair of side surfaces adjacent to the bonding surface, and a resin layer arranged on the surface of the pair of side surfaces of the side member. The battery manufacturing method includes a bonding step of ultrasonically bonding the current collector to the bonding surface of the side surface member. In addition, the battery may further have a laminate sheet covering the electrode body and the side member and heat-welded to the side member, and the manufacturing method for the battery may include a heat-welding step of heat-welding the laminate sheet and the side member after the joining step.
[0011] Hereinafter, the method for producing a battery according to an embodiment of the present disclosure will be described with reference to the drawings. Figures 1 to 5 are schematic cross-sectional views for explaining each step of the method for producing a battery according to an embodiment of the present disclosure.
[0012] -Joining process- Fig. 1 is a schematic cross-sectional view showing a side member and a current collector before a bonding process is performed. As shown in Fig. 1, a side member 2 including a terminal has a bonding surface 2A to be ultrasonically bonded to the current collector, and a pair of side surfaces 2B, 2C adjacent to the bonding surface 2A. A tab film 4 as a resin layer is disposed on the side member 2 so as to cover at least a portion of the surface of the pair of side surfaces 2B, 2C. The electrode body (not shown) has a plurality of laminated current collectors 6, and is disposed so that an end of the current collector 6 contacts the bonding surface 2A of the side member 2 before the bonding process.
[0013] Here, the bonding step in the conventional battery manufacturing method will be described. Fig. 6 is a schematic cross-sectional view for explaining the bonding step in the conventional battery manufacturing method, and Fig. 2 is a schematic cross-sectional view for explaining the bonding step in the battery manufacturing method according to the embodiment of the present disclosure. In the bonding step in the conventional battery manufacturing method, as shown in Fig. 6, a horn 12 is pressed against a current collector 6 arranged so that its end is in contact with the bonding surface of the side member 2 from the opposite side to the side member 2, and ultrasonic vibration is applied from the horn 12 to bond the end of the current collector 6 to the bonding surface of the side member 2. At this time, an anvil 16 is pressed against the surface of the side member 2 opposite to the bonding surface as a presser. In addition, a pair of clamps 24 as pressers are placed on the pair of side surfaces 2B, 2C of the side member 2 from above the tab film 4, and pressure is applied in the directions of arrows 24A and 24B, respectively, to grip the side member 2 with the pair of clamps 24. In the bonding process of the conventional battery manufacturing method, clamps 24 with smooth surfaces pressed against the tab film 4 were used. In this conventional manufacturing method, even if the side member 2 was held through the tab film 4 by a pair of clamps 24, the ultrasonic vibrations from the horn 12 were not transmitted well to the interface between the bonding surfaces of the current collector 6 and the side member 2 due to the low Young's modulus of the tab film 4, resulting in poor bonding performance.
[0014] In contrast, in the manufacturing method of a battery according to an embodiment of the present disclosure, as shown in Fig. 2, a clamp 14 having a plurality of protrusions 140 on a surface that is pressed against the tab film 4 is used as the clamp used in the joining step. When the side member 2 is gripped with the clamp 14, pressure is applied in the directions of arrows 14A and 14B, respectively, and gripping is performed so that the protrusions 140 of the clamp 14 penetrate the tab film 4 and contact a pair of side surfaces. As a result, the side member 2 is well fixed by the clamp 14, and the ultrasonic vibration from the horn 12 is well transmitted to the interface between the joining surfaces of the current collector 6 and the side member 2, resulting in excellent joining performance.
[0015] In the joining step of the manufacturing method of the battery according to the embodiment of the present disclosure, the side member 2 is held with the clamp 14 such that the protrusion 140 of the clamp 14 penetrates the tab film 4 and the protrusion 140 of the clamp 14 forms holes in the surfaces of the pair of side faces 2B, 2C of the side member 2. Therefore, the side member 2 after the joining step shown in FIG. 3 has a plurality of holes 10 in the surfaces of the pair of side faces 2B, 2C.
[0016] -Thermal welding process- Next, a thermal welding step performed after the joining step in the battery manufacturing method according to the embodiment of the present disclosure will be described. 4 and 5 are schematic cross-sectional views for explaining a thermal welding step in a manufacturing method of a battery according to an embodiment of the present disclosure. Although not shown, an end of a current collector is joined to a joining surface 2A of the side member 2 shown in Figs. 4 and 5, and an electrode body connected to the current collector is disposed on the joining surface 2A side of the side member 2 (i.e., the upper side in Figs. 4 and 5).
[0017] 4, first, before carrying out the thermal welding step, a laminate sheet 8 is arranged so as to cover the electrode body (not shown) and a part of the side member 2. Then, a pair of heat bars 18 are applied to a pair of side surfaces 2B, 2C of the side member 2 from above the tab film 4 and laminate sheet 8, and heat is applied while applying pressure in the directions of arrows 18A and 18B, respectively, to thermally weld the laminate sheet 8 to the side member 2 via the tab film 4. At this time, since a plurality of holes 10 are formed in the pair of side surfaces 2B, 2C of the side surface member 2, the resin of the tab film 4 melted by the heat from the heat bar 18 flows into the holes 10. Therefore, the resin of the tab film 4 fills the holes 10 in the side surface member 2 after the heat welding process. This improves the bonding strength between the side surface member 2 and the tab film 4 due to the anchor effect, and also improves the bonding strength between the laminate sheet 8 and the side surface member 2, which are heat-welded via the tab film 4.
[0018] Although Figures 1 to 5 show an embodiment having a current collector 6 in which multiple electrode bodies (not shown) are stacked, the number of current collectors 6 is not particularly limited, and an embodiment having only one current collector 6 may also be used.
[0019] ·protrusion The projection of the clamp is not particularly limited as long as it can penetrate a resin layer such as a tab film in the joining step. For example, the surface of the clamp that contacts the resin layer, such as the tab film, may have a plurality of protrusions arranged in one row, a plurality of protrusions arranged in two rows, or a plurality of protrusions arranged in three or more rows. From the viewpoint of favorably fixing the side member in the joining step, it is preferable that the surface of the clamp contacts the resin layer. Furthermore, when the side member has multiple protrusions arranged in two or more rows, the protrusions may be formed evenly on the side closer to the joining surface and the opposite side when the side member is gripped, but from the viewpoint of obtaining good joining performance in the joining process, it is preferable that the protrusions are formed biased toward the side closer to the joining surface. Furthermore, a plurality of protrusions arranged in one or more rows may be formed evenly from one end to the other end of the clamp, but the protrusions may be formed biased toward one end or the other end.
[0020] Examples of the shape of the protrusions include cones (such as true circular cones and elliptical cones), triangular pyramids (such as regular triangular pyramids and right-angled triangular pyramids), and square pyramids (such as regular square pyramids, pyramids with a diamond base, and pyramids with a rectangular base).
[0021] The height of the protrusion is important in relation to the thickness of the resin layer of the tab film or the like, and is required to be a height that allows the protrusion to penetrate the resin layer and contact the side member. In addition, it is preferable that the height is such that a hole can be formed well in the surface of the side member. From this viewpoint, the height of the protrusion is preferably 100 μm or more and 2000 μm or less, and more preferably 200 μm or more and 1000 μm or less. The height of the protrusion means the distance in the direction perpendicular to the surface from where the protrusion does not exist on the surface of the clamp that contacts the resin layer such as the tab film to the apex of the protrusion.
[0022] From the viewpoint of favorably fixing the side surface member in the joining step, the distance between the projections (that is, the pitch) is preferably 0.2 mm or more and 4 mm or less, and more preferably 0.4 mm or more and 2 mm or less. The distance between the projections means the distance between the apexes of adjacent projections. The distances between the apexes of all adjacent projections on the clamp are measured, and the average value is taken as the distance between the projections.
[0023] <Battery> A battery according to an embodiment of the present disclosure includes an electrode assembly having a current collector, a side member including a terminal and disposed on a side of the electrode assembly, the side member having a bonding surface ultrasonically bonded to the current collector and a pair of side surfaces adjacent to the bonding surface, a resin layer disposed on the surfaces of the pair of side surfaces of the side member, and a laminate sheet covering the electrode assembly and the side member and heat-welded to the side member. The side member has a plurality of holes on the pair of side surfaces, and the resin of the resin layer fills the holes. This improves the bonding strength between the side surface member and the resin layer due to the anchor effect, and also improves the bonding strength between the laminate sheet and the side surface member which are thermally welded via the resin layer.
[0024] ·hole The hole in the side member of the battery is not particularly limited. For example, each of a pair of side surfaces of the side surface member may have a plurality of holes arranged in a row. Also, as shown in Fig. 7, each of a pair of side surfaces 2B, 2C of the side surface member 2 may have a plurality of holes 10 arranged in two rows. Furthermore, as shown in Fig. 8, each of a pair of side surfaces 2B, 2C of the side surface member 2 may have a plurality of holes 10 arranged in three or more rows. From the viewpoint of achieving a good anchor effect, it is preferable to have a plurality of holes arranged in two or more rows. Furthermore, when there are multiple holes arranged in two or more rows, the holes 10 may be formed evenly on the joining surface 2A side and the opposite side of the pair of side surfaces 2B, 2C as shown in Figure 9. However, from the viewpoint of obtaining good joining performance in the joining process, it is preferable that the holes 10 are formed biased toward the joining surface 2A side. In addition, the multiple holes 10 arranged in one or more rows may be evenly formed from one end to the other end of the pair of side surfaces 2B, 2C, or the holes 10 may be biased toward one end and the other end of the pair of side surfaces 2B, 2C as shown in Figure 10.
[0025] Examples of the hole shape include cones (such as true circular cones and elliptical cones), triangular pyramids (such as regular triangular pyramids and right-angled triangular pyramids), and square pyramids (such as regular square pyramids, pyramids with a diamond base, and pyramids with a rectangular base).
[0026] From the viewpoint of achieving a good anchor effect, the depth of the hole is preferably 5 μm or more and 100 μm or less, and more preferably 10 μm or more and 50 μm or less. The depth of the hole means the distance in the direction perpendicular to the surface from the surface of the area where no hole is formed on the pair of side surfaces of the side member to the deepest part of the hole.
[0027] From the viewpoint of achieving a good anchor effect, the distance between the holes (that is, the pitch) is preferably 0.2 mm or more and 2 mm or less, and more preferably 0.4 mm or more and 1 mm or less. The distance between holes means the distance between the deepest points of adjacent holes. The distances between the deepest points of all adjacent holes in a pair of side surfaces of the side member are measured, and the average value is taken as the distance between the holes.
[0028] When a hole 10 is formed on the surface of the side member 2 by the protrusion of the clamp, a bulge 20 is formed on the edge of the hole 10 as shown in FIG. 11. The height of the bulge 20 on the edge of the hole is preferably 1 / 2 or less than the thickness of the resin layer (such as a tab film), and further, when the laminate sheet has a resin layer (so-called a welded resin layer) on the side member side of the metal layer in addition to the metal layer, it is preferably 1 / 2 or less than the total thickness of the resin layer (such as a tab film) and the welded resin layer in the laminate sheet. Specifically, the height of the bulge 20 on the edge of the hole is preferably 40 μm or less, more preferably 20 μm or less. On the other hand, the lower limit of the height of the bulge 20 on the edge of the hole is not particularly limited, and may be 0 μm or more, or may be 2 μm or more. The height of the protuberance 20 at the hole edge means the distance 20H in the direction perpendicular to the surface from the surface of the area in which the hole 10 is not formed on the pair of side surfaces of the side member 2 to the apex of the protuberance 20.
[0029] <Battery components> Next, each component constituting the battery of the present disclosure will be described.
[0030] Laminated sheet The laminate sheet in the present disclosure has at least a metal layer, and preferably further has a weldable resin layer on the side of the metal layer facing the side member. The laminate sheet may also have a protective layer on the side of the metal layer opposite the side member. Examples of materials for the adhesive resin layer include olefin resins such as polypropylene (PP) and polyethylene (PE). Examples of materials for the metal layer include aluminum, aluminum alloys, and stainless steel. Examples of materials for the protective layer include polyethylene terephthalate (PET) and nylon. The thickness of the welded resin layer is, for example, 40 μm or more and 100 μm or less. The thickness of the metal layer is, for example, 30 μm or more and 60 μm or less. The thickness of the protective layer is, for example, 20 μm or more and 60 μm or less. The thickness of the entire laminate sheet is, for example, 70 μm or more and 220 μm or less.
[0031] Resin layer (tab film, etc.) The battery of the present disclosure has a resin layer (e.g., a tab film) disposed on the surface of a pair of side surfaces of the side surface member. The resin layer covers a portion of the surface of the side surface member and is disposed between the side surface member and the laminate sheet. Examples of materials for the resin layer include olefin resins such as polypropylene (PP), polyethylene (PE), etc. The thickness of the resin layer is, for example, 40 μm or more and 100 μm or less.
[0032] Here, the thickness of each layer is defined as the average value of measurements taken at 10 arbitrarily selected points.
[0033] ·Electrode body The electrode assembly in the present disclosure typically has a positive electrode current collector, a positive electrode active material layer, an electrolyte layer, a negative electrode active material layer, and a negative electrode current collector, in this order in the thickness direction.
[0034] The positive electrode active material layer contains at least a positive electrode active material. The positive electrode active material layer may further contain at least one of a conductive material, an electrolyte, and a binder. The positive electrode active material is, for example, in the form of particles. Examples of the positive electrode active material include oxide active materials. Sulfur (S) may also be used as the positive electrode active material.
[0035] The positive electrode active material preferably contains a lithium composite oxide. The lithium composite oxide may contain at least one selected from the group consisting of F, Cl, N, S, Br, and I. The lithium composite oxide may have a crystal structure belonging to at least one space group selected from the space groups R-3m, Immm, and P63-mmc (also called P63mc or P6 / mmc). The lithium composite oxide may have an O2 type structure in which the transition metal, oxygen, and lithium are mainly arranged.
[0036] Examples of lithium composite oxides having a crystal structure belonging to R-3m include Li x Me y O αX β (Me represents at least one selected from the group consisting of Mn, Co, Ni, Fe, Al, Cu, V, Nb, Mo, Ti, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, Ag, Ru, W, B, Si, and P, and X represents at least one selected from the group consisting of F, Cl, N, S, Br, and I, and satisfies 0.5≦x≦1.5, 0.5≦y≦1.0, 1≦α<2, and 0<β≦1.)
[0037] Examples of lithium composite oxides having a crystal structure belonging to Immm include Li x1 M 1 A 1 2(1.5≦x1≦2.3, M 1 contains at least one selected from the group consisting of Ni, Co, Mn, Cu and Fe, and A 1 contains at least oxygen, and A 1 The ratio of oxygen in the oxide is 85 atomic % or more. x1 M 1A 1-x2 M 1B x2 O 2-y A 2 y (0≦x2≦0.5, 0≦y≦0.3, and at least one of x2 and y is not 0; M 1A represents at least one selected from the group consisting of Ni, Co, Mn, Cu and Fe, and M 1B represents at least one selected from the group consisting of Al, Mg, Sc, Ti, Cr, V, Zn, Ga, Zr, Mo, Nb, Ta and W, and A2 represents at least one selected from the group consisting of F, Cl, Br, S and P.
[0038] Examples of lithium composite oxides having a crystal structure belonging to P63-mmc include M1 x M2 yO2 (where M1 represents an alkali metal (preferably at least one of Na and K), M2 represents a transition metal (preferably at least one selected from the group consisting of Mn, Ni, Co, and Fe), and 0 < x + y ≦ 2). Examples include composite oxides represented by this formula.
[0039] As the lithium composite oxide having an O2-type structure, for example, Li x [Li α (Mn a Co b M c ) 1-α O2 (0.5 < x < 1.1, 0.1 < α < 0.33, 0.17 < a < 0.93, 0.03 < b < 0.50, 0.04 < c < 0.33, and M represents at least one selected from the group consisting of Ni, Mg, Ti, Fe, Sn, Zr, Nb, Mo, W, and Bi). Examples include composite oxides represented by this formula, and specific examples include Li 0.744 [Li 0.145 Mn 0.625 Co 0.115 Ni 0.115 O2, etc.
[0040] In addition, the positive electrode preferably contains a solid electrolyte selected from the group of solid electrolytes consisting of sulfide solid electrolytes, oxide solid electrolytes, and halide solid electrolytes in addition to the positive electrode active material. A more preferred embodiment is one in which at least a part of the surface of the positive electrode active material is coated with a sulfide solid electrolyte, an oxide solid electrolyte, or a halide solid electrolyte. As the halide solid electrolyte for coating at least a part of the surface of the positive electrode active material, Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0 < x < 1, 0 < b ≦ 1.5) [LTAF electrolyte] is preferred.
[0041] Examples of the conductive material include carbon materials. The electrolyte may be a solid electrolyte or a liquid electrolyte. The solid electrolyte may be an organic solid electrolyte such as a gel electrolyte, or an inorganic solid electrolyte such as an oxide solid electrolyte or a sulfide solid electrolyte. The liquid electrolyte (electrolytic solution) contains, for example, a supporting salt such as LiPF6 and a solvent such as a carbonate-based solvent. Examples of the binder include a rubber-based binder and a fluoride-based binder.
[0042] The negative electrode active material layer contains at least a negative electrode active material. The negative electrode active material layer may further contain at least one of a conductive material, an electrolyte, and a binder. Examples of the negative electrode active material include metal active materials such as Li and Si, carbon active materials such as graphite, Li4Ti5O 12 The oxide active material may be, for example, a foil or mesh. The conductive material, electrolyte, and binder are the same as those described above.
[0043] The electrolyte layer is disposed between the positive electrode active material layer and the negative electrode active material layer and contains at least an electrolyte. The electrolyte may be a solid electrolyte or a liquid electrolyte. The electrolyte layer is preferably a solid electrolyte layer. The electrolyte layer may have a separator.
[0044] The solid electrolyte preferably contains at least one solid electrolyte species selected from the group of solid electrolytes consisting of sulfide solid electrolytes, oxide solid electrolytes, and halide solid electrolytes.
[0045] As a sulfide solid electrolyte, it is preferably contained sulfur (S) as the main component of the anion element, and further preferably contains, for example, Li element and A element. The A element is at least one selected from the group consisting of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In. The sulfide solid electrolyte may further contain at least one of O and a halogen element. Examples of the halogen element (X) include F, Cl, Br, I, etc. The composition of the sulfide solid electrolyte is not particularly limited, and examples thereof include xLi2S·(100 - x)P2S5 (70 ≦ x ≦ 80), yLiI·zLiBr·(100 - y - z)(xLi2S·(1 - x)P2S5) (0.7 ≦ x ≦ 0.8, 0 ≦ y ≦ 30, 0 ≦ z ≦ 30). The sulfide solid electrolyte may have a composition represented by the following general formula (1). Li 4-x Ge 1-x P x S4(0 < x < 1) ··· Formula (1) In Formula (1), at least a part of Ge may be substituted by at least one selected from the group consisting of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. Also, at least a part of P may be substituted by at least one selected from the group consisting of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. A part of Li may be substituted by at least one selected from the group consisting of Na, K, Mg, Ca, and Zn. A part of S may be substituted by a halogen. The halogen is at least one of F, Cl, Br, and I.
[0046] As an oxide solid electrolyte, it is preferably contained oxygen (O) as the main component of the anion element, and may contain, for example, Li, Q element (Q represents at least one of Nb, B, Al, Si, P, Ti, Zr, Mo, W, and S), and O. Examples of the oxide solid electrolyte include garnet-type solid electrolytes, perovskite-type solid electrolytes, NASICON-type solid electrolytes, Li-P-O-based solid electrolytes, Li-B-O-based solid electrolytes, etc. Examples of the garnet-type solid electrolyte include, for example, Li7La3Zr2O 12 、Li 7-x La3(Zr2-x Nb x )O 12 (0 ≦ x ≦ 2), Li5La3Nb2O 12 and the like. Examples of perovskite-type solid electrolytes include (Li, La)TiO3, (Li, La)NbO3, (Li, Sr)(Ta, Zr)O3, etc. Examples of NASICON-type solid electrolytes include Li(Al, Ti)(PO4)3, Li(Al, Ga)(PO4)3, etc. Examples of Li-P-O-based solid electrolytes include Li3PO4, LIPON (a compound in which part of the O in Li3PO4 is replaced by N), and examples of Li-B-O-based solid electrolytes include Li3BO3, a compound in which part of the O in Li3BO3 is replaced by C, etc.
[0047] As the halide solid electrolyte, a solid electrolyte containing Li, M, and X (M represents at least one of Ti, Al, and Y, and X represents F, Cl, or Br) is suitable. Specifically, Li 6-3z Y z X6 (X represents Cl or Br, and z satisfies 0 < z < 2), Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0 < x < 1, 0 < b ≦ 1.5) is preferred. Among Li 6-3z Y z X6, Li3YX6 (X represents Cl or Br) is more preferred in terms of excellent lithium ion conductivity, and further Li3YCl6 is preferred. Also, Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0 < x < 1, 0 < b ≦ 1.5) is preferably included together with a solid electrolyte such as a sulfide solid electrolyte from the viewpoint of suppressing oxidative decomposition of the sulfide solid electrolyte, etc.
[0048] The positive electrode current collector collects the current of the positive electrode active material layer. Examples of the positive electrode current collector include stainless steel, aluminum, nickel, iron, titanium, and carbon, and aluminum alloy foil or aluminum foil is preferable. The aluminum alloy foil and aluminum foil may be manufactured using powder. The positive electrode current collector may have a shape of, for example, a foil or a mesh. The positive electrode current collector may have a positive electrode tab for connecting to a positive electrode current collector side member.
[0049] The negative electrode current collector collects the current from the negative electrode active material layer. Examples of the material for the negative electrode current collector include metals such as copper, SUS, and nickel. Examples of the shape of the negative electrode current collector include a foil shape and a mesh shape. The negative electrode current collector may have a negative electrode tab for connecting to the negative electrode current collector side member.
[0050] Side members The side member in the present disclosure is disposed on the side portion of the electrode body. Examples of the side member include a current collecting side member. The current collecting side member refers to a side member having a current collecting portion at least in a portion thereof. The current collecting portion is, for example, electrically connected to a tab in the electrode body. The current collecting side member may be the current collecting portion in its entirety, or may be a current collecting portion in its entirety. Examples of materials for the side member include metals such as SUS.
[0051] The shape of the side member is not particularly limited, but may be, for example, a rectangular parallelepiped. When the side member has a rectangular parallelepiped shape, the aspect ratio (As2 / As1) is preferably 0.5 or less, and more preferably 0.3 or less, from the viewpoint of volumetric efficiency. On the other hand, the lower limit of the aspect ratio (As2 / As1) is preferably 0.1 or more, and more preferably 0.2 or more, from the viewpoint of ensuring an area for bonding the current collector. The aspect ratio (As2 / As1) means the ratio of the distance (As2) from the end of one side of a pair of side surfaces 2B and 2C of the side member 2 on the joining surface 2A to the end of the other side of the pair of side surfaces 2B and 2C of the side member 2 on the joining surface 2A, as shown in Figure 1, to the distance (As1) from the end of the pair of side surfaces 2B or 2C of the side member 2 on the joining surface 2A side to the end of the other side of the pair of side surfaces 2B and 2C of the side member 2 on the joining surface 2A side.
[0052] ·Battery structure The structure of the solid-state battery is a laminated structure of a positive electrode / anode / solid electrolyte layer. The solid-state battery includes a so-called all-solid-state battery using a solid electrolyte as an electrolyte, and the solid electrolyte may contain an electrolytic solution of less than 10 mass% with respect to the total amount of the electrolyte. The solid electrolyte may be a composite solid electrolyte containing an inorganic solid electrolyte and a polymer electrolyte.
[0053] The positive electrode has a positive electrode active material layer and a current collector, and the negative electrode has a negative electrode active material layer and a current collector. The solid electrolyte layer may have a single-layer structure or a multi-layer structure having two or more layers. The solid-state battery may have a cross-sectional structure shown in FIG. 12, for example, and the solid electrolyte layer B may have a two-layer structure as shown in FIG. 12. FIG. 12 is a schematic cross-sectional view showing an example of a solid-state battery. The solid-state battery shown in FIG. 12 has a negative electrode including a negative electrode current collector 113 and a negative electrode active material layer A, a solid electrolyte layer B, and a positive electrode including a positive electrode current collector 115 and a positive electrode active material layer C. The negative electrode active material layer A includes a negative electrode active material 101, a conductive assistant 105, and a binder 109. The positive electrode active material layer C includes a coated positive electrode active material 103, a conductive assistant 107, and a binder 111, and the coated positive electrode active material 103 has a surface of a positive electrode active material coated with a LTAF electrolyte or a LiNbO3 electrolyte. The solid-state battery may be configured by sealing the end faces (side faces) of the laminated structure of the positive electrode / solid electrolyte layer / negative electrode with resin. The electrode current collector may have a buffer layer, an elastic layer, or a PTC (Positive Temperature Coefficient) thermistor layer disposed on the surface.
[0054] ·battery The battery in the present disclosure is typically a lithium-ion secondary battery. Examples of uses of the battery include power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (BEVs), gasoline-powered vehicles, and diesel-powered vehicles. In particular, the battery is preferably used as a driving power source for hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), or electric vehicles (BEVs). The battery in the present disclosure may also be used as a power source for moving objects other than vehicles (e.g., railways, ships, and aircraft), and may also be used as a power source for electrical products such as information processing devices.
[0055] The present disclosure is not limited to the above-described embodiments. The above-described embodiments are merely examples, and anything that has substantially the same configuration as the technical idea described in the claims of the present disclosure and exhibits similar effects is included in the technical scope of the present disclosure.
[0056] Here, the effect of the battery according to the present disclosure was confirmed by experiment.
[0057] Comparative Example 1 First, similarly to the configuration shown in FIG. 1, a tab film 4 was placed so as to cover a part of the surface of a pair of side surfaces 2B, 2C of the side member 2, and an end of a current collector 6 was placed so as to contact a joining surface 2A of the side member 2. Next, similarly to the configuration shown in FIG. 6, a horn 12 was pressed against the current collector 6, an anvil 16 was pressed against the surface of the side member 2 opposite to the joining surface, and a pair of clamps 24 was pressed against the pair of side surfaces 2B, 2C of the side member 2 from above the tab film 4 to grip the side member 2. The clamps 24 used had a surface that was pressed against the tab film 4 and had a smooth shape. Then, ultrasonic vibration was applied from the horn 12 to join the end of the current collector 6 to the joining surface of the side member 2 (joining process). 4, a laminate sheet 8 was placed so as to cover the electrode body (not shown) and a part of the side member 2. Then, a pair of heat bars 18 were pressed against a pair of side surfaces 2B, 2C of the side member 2 from above the tab film 4 and the laminate sheet 8 while heating, thereby thermally welding the laminate sheet 8 to the side member 2 via the tab film 4 (thermal welding process). In this manner, a battery was manufactured.
[0058] ·Reference example 1 A battery was manufactured in the same manner as in Comparative Example 1, except that no tab film was used and bonding was performed by pressing the pair of clamps 24 directly against the pair of side surfaces 2B, 2C of the side surface member 2 in the bonding step.
[0059] Example 1 A battery was produced in the same manner as in Comparative Example 1, except for the following changes. As the clamp in the joining step, a clamp 14 having a protrusion on the surface pressed against the tab film 4 was used, similar to the configuration shown in FIG. 2. When the side member 2 was held by the clamp 14, pressure was applied in the directions of the arrows 14A and 14B, respectively, so that the protrusion 140 of the clamp 14 penetrated the tab film 4 and the protrusion 140 of the clamp 14 formed holes in the surfaces of the pair of side faces 2B and 2C of the side member 2. Therefore, similar to the configuration shown in FIG. 3, the side member 2 after the joining step had a plurality of holes 10 in the surfaces of the pair of side faces 2B and 2C. Thereafter, in the thermal welding step, the resin of the tab film 4 melted by the heat from the heat bar 18 flowed into the holes 10 in the pair of side faces 2B and 2C of the side member 2.
[0060] The projections on the clamp were as follows: ·Two rows of clamp tabs on the surface that comes into contact with the film - Shape of protrusion: Cone Height of protrusion: 1000μm - Distance between protrusions (pitch): 2mm The holes formed in the side members were as follows: - Two rows on a pair of side surfaces of side members Hole Shape: Cone Hole depth: 15μm Hole spacing (pitch): 2mm Height of the bump at the edge of the hole: 5μm
[0061] -Evaluation of bonding performance For the batteries of Comparative Example 1, Reference Example 1, and Experimental Example 1, the bonding strength between the bonding surface of the current collector and the side member was measured by the following method. Using a tensile tester shown in Fig. 13, the side member 2 and the current collector (a current collector formed by stacking 60 current collector foils) 6 were clamped by upper chuck 32A and lower chuck 32B, respectively. A tensile test was carried out at a tensile speed of 5 mm / s in the direction in which a shear stress was applied to the bonding surface where the bonding portion 60 of the current collector 6 was bonded, and the bonding strength (N) was determined.
[0062] [Table 1]
[0063] As shown in Table 1, in Example 1, in which a clamp having a protrusion was used to grip the side member so that the protrusion penetrated the tab film and formed a hole in the surface of the side member, superior bonding performance was obtained compared to Comparative Example 1, in which a clamp having a smooth shape was used. [Explanation of symbols]
[0064] 2 Side members 2A joint surface 2B, 2C Pair of sides 4 Tab Film 6 Current collector 12 Horn 14, 24 Clamp 140 Protrusion 16 Anvil 18 Heat Bar 101 Negative electrode active material 103 Coated positive electrode active material 105, 107 Conductive additives 109, 111 Binder 113 Negative electrode current collector 115 Positive electrode current collector A negative electrode active material layer B Solid electrolyte layer C positive electrode active material layer
Claims
1. An electrode assembly having a current collector; a side member including a terminal, the side member being disposed on a side surface of the electrode body, the side member having a joining surface to be ultrasonically joined to the current collector, and a pair of side surfaces adjacent to the joining surface; a resin layer disposed on a surface of the pair of side surfaces of the side surface member; A method for manufacturing a battery, comprising the steps of: a joining step of ultrasonically joining the current collector to the joining surface of the side member, the joining step is a step of ultrasonically joining the pair of side surfaces of the side surface member while holding the pair of side surfaces of the side surface member from above the resin layer with a pair of clamps having a plurality of protrusions, The method for manufacturing a battery, wherein the clamping is performed so that the protrusions of the clamp penetrate the resin layer and contact the pair of side surfaces.
2. the battery has a laminate sheet covering the electrode body and the side member, The joining step includes forming holes in the surfaces of the pair of side surfaces by the protrusions of the clamp during the holding step, A thermal welding step of thermally welding the laminate sheet and the side member is provided after the joining step, The method for manufacturing a battery according to claim 1 , wherein the resin of the resin layer penetrates into the holes after the thermal welding step.
3. An electrode assembly having a current collector; a side member including a terminal, the side member being disposed on a side surface of the electrode body, the side member having a joining surface that is ultrasonically joined to the current collector, and a pair of side surfaces adjacent to the joining surface; a resin layer disposed on a surface of the pair of side surfaces of the side surface member; a laminate sheet covering the electrode body and the side surface member and heat-welded to the side surface member; The side surface member has a plurality of holes on the pair of side surfaces, The resin of the resin layer penetrates into the holes.
Citation Information
Patent Citations
Jointing method of electrode and electrode junction
JP2005327677A
Joint device of electrode collector and electrode tab
JP2019153496A
Ultrasonic bonding method
JP2022073690A
Battery connections and metalized film components in energy storage devices having internal fuses
WO2021108119A1